Clinical, virological and immunological responses in Danish HIV patients receiving raltegravir as part of a salvage regimen - Engsig, Frederik N; Gerstoft, Jan; Kronborg, Gitte; Larsen, Carsten S; Pedersen, Gitte; Audelin, Anne M; Jørgensen, Louise B; Obel, Niels (Clinical epidemiology, 2010)
Raltegravir is the first integrase inhibitor approved for treatment of HIV-infected patients harboring multiresistant viruses. From a Danish population-based nationwide cohort of HIV patients we identified the individuals who initiated a salvage regimen including raltegravir and a matched cohort of HIV-infected patients initiating HAART for the first time. We compared these two cohorts for virological suppression, gain in CD4 count, and time to first change of initial regimen. We identified 32 raltegravir patients and 64 HIV patients who initiated HAART for the first time in the period 1 January 2006 to 1 July 2009. The virological and immunological responses in the raltegravir patients were comparable to those seen in the control cohort. No patients in the two cohorts died and no patients terminated raltegravir treatment in the observation period. Time to first change of initial regimen was considerably shorter for HAART-naïve patients. We conclude that salvage regimens including raltegravir have high effectiveness in the everyday clinical setting. The effectiveness of the regimens is comparable to that observed for patients initiating HAART for the first time. The risk of change in the salvage regimens after initiation of raltegravir is low.